2016
DOI: 10.1615/critrevtherdrugcarriersyst.2016016272
|View full text |Cite
|
Sign up to set email alerts
|

Oral Squamous Cell Carcinoma: Current Treatment Strategies and Nanotechnology-Based Approaches for Prevention and Therapy

Abstract: Oral squamous cell carcinoma (OSCC) is the most common type of oral cancer; it involves damage to oral epithelial cells due to accumulation of multiple genetic mutations in the cells. OSCC remains major cause of morbidity and mortality in patients with head and neck cancers. Tobacco, smoking, alcohol consumption alone or with chewing tobacco, and betel quid are potential carcinogens contributing to the high occurrence of OSCC. Current treatment modalities for OSCC like chemoradiotherapy, surgery, EGFR inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
124
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(128 citation statements)
references
References 150 publications
0
124
0
4
Order By: Relevance
“…Cur microemulsions were more cytotoxic than a free Cur formulation, and cell viability further decreased with the addition of ultrasound [44]. Mucoadhesive polycaprolactone (PCL) NPs loaded with Cur were also obtained by coating them with chitosan (CS) for local therapy of oral cavity SCC [34,45].These Cur-NPs induced apoptotic death of tongue tumor cells and were less cytotoxic than a free Cur formulation [45].…”
Section: Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…Cur microemulsions were more cytotoxic than a free Cur formulation, and cell viability further decreased with the addition of ultrasound [44]. Mucoadhesive polycaprolactone (PCL) NPs loaded with Cur were also obtained by coating them with chitosan (CS) for local therapy of oral cavity SCC [34,45].These Cur-NPs induced apoptotic death of tongue tumor cells and were less cytotoxic than a free Cur formulation [45].…”
Section: Curcuminmentioning
confidence: 99%
“…However, to date, no NP-based treatment has been approved for HNSCC [31,32]. Clinical trials have been performed and other trials are currently underway to treat advanced HNSCC [31,33,34]. As an example, a liposomal Dox (Doxil/Caelix®) was explored in certain instances of HNSCC [33,35,36].…”
mentioning
confidence: 99%
“…OSCC is the most prevalent form of cancer worldwide, especially in developing regions such as Southeast China (Gharat et al, ). Several previous studies have suggested a close link between mitochondrial fission and cisplatin sensitivity in OSCC cells (Fan et al, , b; Li et al, ), indicating a role for mitochondrial fission in the progression of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…As the sixth most prevalent malignancy worldwide, oral cancer is a major global health issue . The most common type of oral cancer, oral squamous cell carcinoma (OSCC), results from an accumulation of multiple genetic mutations that ultimately causes damage to oral epithelial cells . OSCC remains the major cause of head and neck cancer‐associated morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%